German Bond Yields and Debt Supply : Is There a 'Bund Premium'? - Paret, Anne-Charlotte (IMF Working Papers; Working Paper ;, 2019)
Are Bunds special? This paper estimates the 'Bund premium' as the difference in convenience yields between other sovereign safe assets and German government bonds adjusted for sovereign credit risk, liquidity and swap market frictions. A higher premium suggests less substitutability of sovereign bonds. We document a rise in the 'Bund premium' in the post-crisis period. We show that there is a negative relationship of the premium with the relative supply of German sovereign bonds, which is more pronounced for higher maturities and when risk aversion proxied by bond market volatility is high. Going forward, we expect German government debt supply to remain scarce, with important implications for the ECB's monetary policy strategy.